مؤشرات الأداء الضريبي في الموازنة الفدرالية ودورها في ترشيد توجهات إصلاح النظام الضريبي في العراق: دراسة مقارنة للموازنة الفدرالية للعامين 2006و2 - منى سالم حسين مرعي (PROSPECTIVE RESEARCHES, 2023)
The research dealt with tax performance indicators in the federal budget and its role in rationalizing the directions of reforming the tax system in Iraq. The role of performance indicators in determining the areas of reform was explained. One of the main reasons is the lack of tax awareness among both tax administration and taxpayer. In improving the overall picture of the performance of the tax system in all areas and in order to achieve the objectives of the tax system and reform is mainly related to the ability of those working on tax legislation and tax policy in building the structure of the tax system in Iraq and achieve efficiency and counting the most important conclusions were to identify the shortcomings of the current system in two main areas: The current system lacks flexibility to adapt to economic conditions and deal with new developments. - The lack of a sound and fast tax administration policy that is free from prejudice and exaggeration, in addition to the administration's reliance on arbitrary discretion in determining the amounts of taxation. The most important recommendations were: Adoption of the proposed reform indicators, including the preparation of an electronic collection system to facilitate the collection process and reduce corruption and extortion experienced by the taxpayer when dealing with several parties to determine the tax base and linking the electronic collection system with the e-government system to tighten the taxpayer to pay the tax without delay through Direct deduction.